Erk activation as a possible mechanism of transformation of subependymal nodule into subependymal giant cell astrocytoma - Siedlecka, Monika; Szlufik, Stanislaw; Grajkowska, Wieslawa; Roszkowski, Marcin; Jóźwiak, Jarosław (Folia Neuropathologica, 2015)
Introduction: Subependymal nodule (SEN) and subependymal giant cell astrocytoma (SEGA) are brain lesions frequently found in tuberous sclerosis (TS). As about 10-15% of SENs enlarge and transform into SEGAs, we examined here the possible mechanism of the phenomenon. Material and methods : Using Western blot we studied 1 SEN and 3 SEGA samples; SEN and 1 SEGA came from the same TS patient. We evaluated e.g. the activation of the phosphorylated forms of proteins belonging to Akt, Erk and mTOR pathways. Results: Differences in Erk pathway activation between SEN and SEGA were found. There was no upregulation of p-Erk, p-Mek or p-RSK1 in the SEN specimen, whilst we found these proteins to be significantly uptriggered in SEGA samples. Also, for the first time, we found p-Akt, p-GSK3 and p-PDK1 upregulated in both SEN and SEGA from the same TS patient. Conclusions : Our current study shows for the first time the possible mechanism of SEN/SEGA transformation, where Erk pathway hyperactivation seems to be significant. We hypothesize that SEN/SEGA transformation may depend on Erk potentiation.